Kinerja Keuangan KUD Mambal di Kecamatan Abiansemal, Kabupaten Badung - RAMENAYANTHI, KOMANG TRI; SUAMBA, I KETUT; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Financial Performance of Village Cooperative (KUD) Mambal in Abiansemal District, Badung Regency Agricultural cooperatives in Indonesia through Village Cooperative (KUD) have got the task as well as a wide range of facilities to support the development of rural economy. In the development efforts of KUD in the future, it requires financial information in order to determine the financial performance of a KUD more accurately and completely The aim of this study was to determine the financial performance of KUD Mambal using financial ratio analysis seen from the ratio of liquidity, solvency, activity and profitability from 2010 to 2014 and to determine the factors that affect the financial condition of KUD Mambal. Based on the results of the financial analysis, the liquidity ratio showed the average current ratio was considered to be poor and quick ratio was considered to be less good. The solvency ratio showed the average debt to assets ratio was considered bad and the average debt to equity ratio is considered to bad. Activity ratio shows the average collection period was considered to be less satisfactory, inventory turnover was considered less satisfactory, and fixed asset turnover was considered very good. Profitability ratio showed that the average gross profit margin was considered to be less satisfactory, return on assets was considered less satisfactory, and net profit margin was considered good enough. Suggestions in this research are that KUD Mambal management should consider policies to manage accounts receivable and inventory, as well as services to members should be re-increased. Keywords: Agricultural cooperatives, financial performance, financial analysis